Kajian Analisis Kesesuaian Lahan Wisata Pantai Pohon Cinta Dan Pulau Lahe - Suci Badriani Ohi; Fitryane Lihawa; Ahmad Zainuri (Universitas Lambung Mangkurat, 2020)
The objective of this research is to determine the land suitability in Pohon Cinta Beach and Lahe Island as Beach Tourism in Marisa Sub-District. The methodology employed in this research a survey and documentation methods. The sample is selected by using purposive sampling technique. Data analysis focused on suitability matrix related to land suitability parameters at the beach, i.e., water depth, beach type, width of beach, water bottom material, current velocity, beach slope, water brightness, land cover, hazardous sea creatures, and fresh water availability. Scores and weights are given for each land suitability parameter. Land suitability level is calculated using the formula Beach Tourism Suitability Index. The results indicated that Pohon Cinta Beach has the suitable category (S2), whereas Lahe Island has very suitable category (S1). The results of this study can support local governments in decision making and planning in tourism.